Defect-rich N/S-co-doped porous hollow carbon nanospheres derived from fullerenes as efficient electrocatalysts for the oxygen-reduction reaction and Zn–air batteries. (29th September 2021) - He, Zhimin; Wei, Peng; Xu, Ting; Han, Jiantao; Gao, Xuejiao; Lu, Xing
Abstract : Fullerene-derived N, S-co-doped porous hollow carbon nanospheres with tailored N, S dopants and abundant defects serve as efficient electrocatalysts for the oxygen-reduction reaction and Zn–air batteries. Abstract : The rational design of the electronic properties and geometric structure of the carbon matrix is an effective strategy to develop high-performance carbon-based electrocatalysts toward the oxygen-reduction reaction (ORR). Herein, hollow carbon nanospheres are synthesized using fullerene (C60 ) and ethylenediamine, which then form nitrogen and sulfur co-doped porous hollow carbon nanospheres (N, S-PHCNSs) via direct pyrolysis in the presence of sulfur. The decomposition of fullerenes provides carbon matrix defects, and the use of sulfur effectively modifies the contents and the configurations of the N species in the N, S-PHCNSs along with successful sulfur doping. The optimal N, S-PHCNSs exhibit an excellent ORR performance that is comparable to commercial Pt/C, which is further confirmed by Zn–air batteries. Theoretical calculations suggest that graphitic-N and thiophene-S co-doped pentagon defects can greatly elevate the ORR activity. This work not only presents a facile and effective strategy to regulate the electronic properties of the carbon matrix but also provides useful guidance for the rational design of advanced carbon-based electrocatalysts.